Complexation Strategies for Enhancing Water-Soluble Protein Stability and Functionality: A Comprehensive Review - Qing Guo; Xu Qi; Yuying Hu (Foods, 2025)
Water-soluble proteins, as ideal ingredients in food systems, have attracted much attention. However, their applications in the food industry are still limited by inherent shortcomings in stability and functionalities. Complexation with ligands is an effective strategy to overcome these limitations. In the present review, we summarize (1) the interaction mechanisms between water-soluble proteins and ligands; (2) the enhancement of the stability and functionalities of water-soluble proteins; (3) the influences of the nature of proteins and ligands, along with complexing conditions, on their interactions and enhancement of the stability and functionalities of water-soluble proteins; and (4) the applications of water-soluble protein-based complexes. Promising future research trends in the field of water-soluble protein-based complexes are also discussed. This review aims to offer theoretical guidance and technical support for the precise enhancement of protein stability and functionalities, thereby promoting their broader application in the food industry.